Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
Theo bài ra ta có :
\(\left(x+7\right)\left(3x-1\right)-x^2+49=0\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)-\left(x^2-49\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)-\left(\left(x-7\right)\left(x+7\right)\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1-x+7\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(2x+6\right)=0\)
\(\Leftrightarrow\left[\begin{matrix}x+7=0\\2x+6=0\end{matrix}\right.\)
\(\Leftrightarrow\left[\begin{matrix}x=-7\\x=-3\end{matrix}\right.\)
Vậy \(S=\left\{-3;-7\right\}\)
Chúc bạn học tốt =))
a/
<=>(x+7)(3x-1)-(x^2-7^2)=0
<=>(x+7)(3x-1)-(x-7)(x+7)=0
<=>(x+7)(3x-1-x+7)=0
<=>(x+7)(2x+6)=0
<=>x+7=0 hoặc 2x+6=0
<=>x=-7 2x=-6
<=> x=-3
=>S (-7;-3)
\(a,\left(x+7\right)\left(3x-1\right)=x^2-49\)
\(\left(x+7\right)\left(3x-1\right)-\left(x+7\right)\left(x-7\right)=0\)
\(\left(x+7\right)\left(3x-1-x+7\right)=0\)
\(\left(x+7\right)\left(2x+6\right)=0\)
\(\hept{\begin{cases}x+7=0\\2x+6=0\end{cases}}\)
\(\hept{\begin{cases}x=-7\\x=-3\end{cases}}\)
\(b,5\left(x-3\right)-4=2\left(x-1\right)+7\)
\(5x-15-4=2x-2+7\)
\(5x-19=2x+5\)
\(3x=24\)
\(x=8\)
\(x\left(x-2\right)\left(x+2\right)-\left(x-3\right)\left(x^2+3x+9\right)\)
\(=\left(x^2-2x\right)\left(x+2\right)-\left(x-3\right)\left(x^2+3x+9\right)\)
\(=x^3+2x^2-2x^2-4x-x^3-3x^2-9x+3x^2+9x+27\)
\(=9x-4x+27=5x+27\)
\(\left(2x+7\right)\left(4x^2-14x+49\right)-2x\left(2x-1\right)\left(2x+1\right)\)
\(=\left(2x+7\right)\left(4x^2-14+49\right)-\left(4x^2-2x\right)\left(2x+1\right)\)
\(8x^3-28x+98x+28x^2-98+343-8x^3-4x^2+4x^2+2x\)
\(\left(98x-28x+2x\right)+343=72x+343\)
b: \(\Leftrightarrow\dfrac{7x+10}{x+1}\left(x^2-x-2-2x^2+3x+5\right)=0\)
\(\Leftrightarrow\left(7x+10\right)\left(-x^2+2x+3\right)=0\)
\(\Leftrightarrow\left(7x+10\right)\left(x^2-2x-3\right)=0\)
=>(7x+10)(x-3)=0
hay \(x\in\left\{-\dfrac{10}{7};3\right\}\)
d: \(\Leftrightarrow\dfrac{13}{2x^2+7x-6x-21}+\dfrac{1}{2x+7}-\dfrac{6}{\left(x-3\right)\left(x+3\right)}=0\)
\(\Leftrightarrow\dfrac{13}{\left(2x+7\right)\left(x-3\right)}+\dfrac{1}{\left(2x+7\right)}-\dfrac{6}{\left(x-3\right)\left(x+3\right)}=0\)
\(\Leftrightarrow26x+91+x^2-9-12x-14=0\)
\(\Leftrightarrow x^2+14x+68=0\)
hay \(x\in\varnothing\)
Ta có: \(\left(x+7\right)\left(3x-1\right)=49-x^2\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)=\left(7-x\right)\left(7+x\right)\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)-\left(7-x\right)\left(x+7\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1-7+x\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(4x-8\right)=0\)
\(\Leftrightarrow\left(x+7\right)\cdot4\cdot\left(x-2\right)=0\)
Vì 2≠0
nên \(\left[{}\begin{matrix}x+7=0\\x-2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-7\\x=2\end{matrix}\right.\)
Vậy: x∈{-7;2}
\(\left(x+7\right)\left(3x-1\right)=49-x^2\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)=\left(x+7\right)\left(7-x\right)\)
\(\Leftrightarrow3x-1=7-x\)
\(\Leftrightarrow4x=8\Leftrightarrow x=2\)
Vậy...
Ta có :
\(\left(x+7\right)\left(3x-1\right)=49-x^2\)
\(\Leftrightarrow\)\(\left(x+7\right)\left(3x-1\right)=7^2-x^2\)
\(\Leftrightarrow\)\(\left(x+7\right)\left(3x-1\right)=\left(x+7\right)\left(7-x\right)\)
\(\Leftrightarrow\)\(\left(x+7\right)\left(3x-1\right)-\left(x+7\right)\left(7-x\right)=0\)
\(\Leftrightarrow\)\(\left(x+7\right)\left(3x-1-7+x\right)=0\)
\(\Leftrightarrow\)\(\left(x+7\right)\left(4x-8\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x+7=0\\4x-8=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-7\\4x=8\end{cases}}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=-7\\x=\frac{8}{4}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-7\\x=2\end{cases}}}\)
Vậy \(x=2\) hoặc \(x=-7\)
Chúc bạn học tốt ~
Ta có: (x+7)(3x-1)=49-x^2
\(\Rightarrow\left(x+7\right)\left(3x-1\right)-49+x^2=0\)
\(\Rightarrow4x^2+20-56=0\)
\(\Rightarrow\left(2x\right)^2+2.2x.5+5^2-81=0\)
\(\Rightarrow\left(2x+5\right)^2=81\)
\(\Rightarrow2x+5=9\)hoặc \(2x+5=-9\)
\(\Rightarrow x=2\)hoặc \(x=-7\)